Analysis of Community-Based Coffee Agro-tourism Sustainability in East Java, Indonesia - Hidayat, Fajar Rasyiidi; Luchman Hakim; Parmawati, Rita (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2023)
Agro-tourism is the potential sector that can be developed in rural areas for local economic enhancement, contributing to conservation, and awarding local wisdom. However, several problems in development cause agro-tourism not to be sustainable. This research aimed to describe the existing condition and assess the sustainability of coffee agro-tourism. We evaluate the existing condition and sustainability status by assessing ancillary, attractions, accessibility, amenities, economy, ecology and socio-culture. Respondents from this research were 141 respondents, and each respondent was interviewed with a questionnaire. Data analysis was conducted with two methods: descriptive analysis and MDS (Multidimensional Scaling). Existing conditions from the institutional aspect show that some agro-tourism does not have institutional legality, the main attraction is coffee plantations, accessibility is challenging to reach, amenities do not yet have quality according to standards, economic actors are the community, public perception of agro-tourism is very positive. MDS analysis status is very sustainable regarding economic aspects, with a score index of 76.82 %. Ecology, amenities, attractions, social culture and ancillary aspects show enough sustainable status with a score index of 71.01%, 67.73%, 67.59%, 67.58% and 59.97%. At the same time, the accessibility aspect shows a less sustainable status with an index of 33.49%. The results of the leverage analysis show 29 sensitive attributes are an influential key factor in sustainability.